Monoclonal Gammopathy of Renal Significance: Clinical and Histological Efficacy of a Bortezomib-Based Regimen - Quattrocchio, Giacomo; Barreca, Antonella; Vaccarino, Antonella; Del Vecchio, Giulio; De Simone, Emanuele; Fenoglio, Roberta; Ferro, Michela; Pagliaro, Maria; Pini, Massimo; Manes, Massimo; Roccatello, Dario (Frontiers in Medicine, 2020)
Monoclonal Gammopathy of Renal Significance (MGRS) is a group of heterogeneous disorders characterized by renal dysfunction secondary to the production of a monoclonal immunoglobulin by a nonmalignant B cell or plasma cell clone. We report the clinical and histological outcomes of two patients with biopsy-proven MGRS: one patient showed membranoproliferative glomerulonephritis with monoclonal k-light chain and C3 deposits, the second patient showed immunotactoid glomerulopathy. Both patients were treated with a 9-month chemotherapy protocol including bortezomib, cyclophosphamide and dexamethasone. Renal biospy was repeated after 1 year. The estimated glomerular filtration rate (eGFR) increased from 22.5 (baseline) to 40 ml/min per 1.73 m2 after 12 months, then to 51.5 ml/min per 1.73 m2 after 24 months; proteinuria decreased from 4.85 (baseline) to 0.17 g/day after 12 months, then to 0.14 g/day after 24 months. Repeat renal biopsies showed a dramatic improvement of the glomerular proliferative lesions and near complete disappearance of the immune deposits. A bortezomib-based treatment proved very effective and was well tolerated in the two patients presenting with clinically and histologically aggressive MGRS.